Evolutionary dynamics of Usutu virus: Worldwide dispersal patterns and transmission dynamics in Europe - Marina Siljic; Rastko Sehovic; Marko Jankovic; Gorana Stamenkovic; Ana Loncar; Marija Todorovic; Maja Stanojevic; Valentina Cirkovic (Frontiers in Microbiology, 2023)
BackgroundUsutu virus (USUV) is an emerging mosquito-borne Flavivirus, with birds as the main zoonotic reservoir. Humans are accidental hosts and mostly develop mild or even asymptomatic infections, although severe complications such as encephalitis can also arise. Detailed characterization of the pathogen's phylogenetics may offer valuable insights into the prediction and prevention of potential epidemics; however, lack of uniformity and the number of available USUV sequences worldwide hamper comprehensive investigation.AimThe study aimed to investigate USUV spatio-temporal dispersal inter- and intracontinentally and to estimate the dynamics of viral spread within Europe.MethodsPhylogeographic and phylodynamic analyses were done using advanced phylogenetic methods implemented in Beast 1.10.4 and Beast 2.6.4 software packages.ResultsHerein, we report on a new USUV isolate from Culex pipiens collected in 2019 from Serbia. The results of this research revealed two newly described intercontinental migration events of USUV from Africa to Germany in the 1970s and from Africa to the Middle East (Israel) in the late 90s. Finally, phylodynamic analysis substantiated the ongoing active expansion of USUV in Europe.ConclusionThe data would imply a high potential for further USUV expansion in Europe. Detailed phylogenetic characterization of the pathogen may offer valuable insights into prediction and prevention of potential epidemics; however, lack of uniformity and number of available USUV sequences worldwide hampers comprehensive investigation. This study draws attention to the need for upscaling USUV surveillance.